When Suicide Kills: An Empirical Analysis of the Lethality of Suicide Terrorism - Alakoc, Burcu Pinar (International Journal of Conflict and Violence (IJCV), 2017)
Why are some suicide terrorist attacks deadlier than others? Suicide bombers, unlike stationary bombs, are self-guided human weapons; they can deliver and detonate explosives at a specific time and place with precision. Coding and analyzing new data on over four hundred suicide terrorist incidents from all around the world between 1998 and 2015, this paper argues that the number of fatalities resulting from suicide attacks is a function of strategic choices made by the perpetrators, such as where to attack and whom to target. Results of this analysis show that suicide attacks that seize targets of opportunity are the most lethal. Specifically, suicide attacks that target civilians in enclosed and easily accessible places, and that are undertaken by multiple perpetrators result in the highest numbers of fatalities. Understanding these strategic tactical attributes of suicide terrorism is fundamental to devising effective counterterrorism strategies that aim at hardening soft targets and minimizing the lethal impact of these attacks.